2023
DOI: 10.34108/eujhs.1177917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Change in Nutrition After Laparoscopic Cholecystectomy

Kıymet ÖZTEPE,
İkbal ÇAVDAR,
Nihat AKSAKAL

Abstract: This prospective descriptive study was conducted to evaluate the changing nutritional habits of patients who underwent laparoscopic cholecystectomy. The study was carried out 76 patients between December 2019-May 2021. The data were collected using ‘Nutritional Habit Diagnosis Form’ by interviewing the patients three months after surgery by telephone. While age and gender factors were found to affect nutritional habits after laparoscopic cholecystectomy, the rate of development of symptoms related to nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Öztepe et al found that after laparoscopic cholecystectomy, symptoms worsened with the consumption of processed meats, full-fat cheese, some fruits and vegetables, snack foods, sauces, and fried, high-fat foods. This emphasizes how crucial it is to assess dietary practices prior to surgery and offer post-operative dietary advice [19].…”
Section: Srmentioning
confidence: 99%
“…Öztepe et al found that after laparoscopic cholecystectomy, symptoms worsened with the consumption of processed meats, full-fat cheese, some fruits and vegetables, snack foods, sauces, and fried, high-fat foods. This emphasizes how crucial it is to assess dietary practices prior to surgery and offer post-operative dietary advice [19].…”
Section: Srmentioning
confidence: 99%